2018
DOI: 10.1177/0003319717752245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Preprocedural Laboratory Parameters as Predictors of Drug-Eluting Stent Restenosis in Coronary Chronic Total Occlusion Lesions

Abstract: This retrospective, single-center study assessed the prognostic value of several emerging inflammatory markers as predictors of in-stent restenosis (ISR) after drug-eluting stent implantation for coronary chronic total occlusion (CTO) lesions. Consecutive patients (n = 416) who underwent successful percutaneous coronary intervention (PCI) for documented CTO lesions and with follow-up angiography were enrolled. Preprocedural high-sensitivity C-reactive protein (hsCRP), neutrophil-to-lymphocyte ratio (NLR), plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
(36 reference statements)
1
36
0
Order By: Relevance
“…C-reactive protein (CRP) is a widely used index of inflammation, and many studies show its associations with restenosis. 7 As shown in our study, the relationship between NLR and CRP was analyzed, and a positive correlation was found. 13 Diabetes and hyperlipidemia are known risk factors for atherosclerosis and restenosis.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…C-reactive protein (CRP) is a widely used index of inflammation, and many studies show its associations with restenosis. 7 As shown in our study, the relationship between NLR and CRP was analyzed, and a positive correlation was found. 13 Diabetes and hyperlipidemia are known risk factors for atherosclerosis and restenosis.…”
supporting
confidence: 61%
“…3,4 Many studies have shown its association with many cardiovascular diseases, 5,6 including stent restenosis. [7][8][9] However, the NLR is not specific, affected by the state of inflammation in the body, such as chronic obstructive pulmonary disease, 10 liver cirrhosis, and gastric ulcer. 11,12 We agree with the comment that other inflammatory diseases should be identified.…”
mentioning
confidence: 99%
“…Indeed, in ammation plays an indispensable role in the pathogenesis of atherosclerosis, and an elevation in in ammatory biomarkers represents the activation of coronary artery damage [14]. Mounting evidence suggests that in ammation, including pre-existing systemic in ammation, local vascular in ammation secondary to PCI, plays a central role in promoting neointimal growth and in-stent restenosis [16,22].…”
Section: Discussionmentioning
confidence: 99%
“…Total white blood cells, neutrophil, lymphocyte, and platelet counts, RDW, MPV were calculated using an automated blood cell counter (Model XE2100; Sysmex, Kobe, Japan). The NLR was computed using the absolute neutrophil count divided by the lymphocyte count, the PLR was calculated by dividing the platelet count by the absolute lymphocyte count [16].…”
Section: Measurements Of Related Parametersmentioning
confidence: 99%
See 1 more Smart Citation